Activation of the c‐Jun N‐terminal kinase pathway aggravates proteotoxicity of hepatic mutant Z alpha1‐antitrypsin. Issue 6 (10th April 2017) - Pastore, Nunzia; Attanasio, Sergio; Granese, Barbara; Castello, Raffaele; Teckman, Jeffrey; Wilson, Andrew A.; Ballabio, Andrea; Brunetti‐Pierri, Nicola
Abstract : Alpha1‐antitrypsin deficiency is a genetic disease that can affect both the lung and the liver. The vast majority of patients harbor a mutation in the serine protease inhibitor 1A ( SERPINA1 ) gene leading to a single amino acid substitution that results in an unfolded protein that is prone to polymerization. Alpha1‐antitrypsin defciency‐related liver disease is therefore caused by a gain‐of‐function mechanism due to accumulation of the mutant Z alpha1‐antitrypsin (ATZ) and is a key example of an disease mechanism induced by protein toxicity. Intracellular retention of ATZ triggers a complex injury cascade including apoptosis and other mechanisms, although several aspects of the disease pathogenesis are still unclear. We show that ATZ induces activation of c‐Jun N‐terminal kinase (JNK) and c‐Jun and that genetic ablation of JNK1 or JNK2 decreased ATZ levels in vivo by reducing c‐Jun–mediated SERPINA1 gene expression. JNK activation was confirmed in livers of patients homozygous for the Z allele, with severe liver disease requiring hepatic transplantation. Treatment of patient‐derived induced pluripotent stem cell‐hepatic cells with a JNK inhibitor reduced accumulation of ATZ. Conclusion : These data reveal that JNK is a key pathway in the disease pathogenesis and add new therapeutic entry points for liver disease caused by ATZ. (Hepatology 2017;65:1865‐1874).